Upaya Diplomasi Budaya Indonesia melalui Rumah Budaya Indonesia di Malaysia - Setiawan, Teguh; Harza, Zulkifli; Jamilah, Maryam (Palito, 2025)
In Indonesia, each region has its own distinct culture, such as traditional dress, traditional lineage system, food and dance. This makes culture an identity. Culture is an important element in the development process or sustainability of a nation. In developed societies, cultural change usually occurs through discovery in the form of new creations (innovation) and through the process of diffusion. This research is a qualitative study with a literature study. The research was analyzed using the conceptual framework of cultural diplomacy. As a state apparatus that has a mission and goal to realize and improve effective and productive cultural diplomacy, the Ministry of Education and Culture (Kemendikbud) initiated the establishment of an Indonesian cultural center called RBI (Rumah Budaya Indonesia). RBI is a place to promote Indonesian culture to other countries to improve the image, appreciation and build friendship through culture with the international community towards Indonesia. RBI is made as a representation of Indonesia, a place to get to know the culture that Indonesia has abroad. RBI has been present in 10 countries, namely Timor Leste, the United States, Australia, the Netherlands, Japan, Germany, South Korea, France, Malaysia, and Turkey. Then in 2017 the RBI program was born in Malaysia.